WOMEN EMPOWERMENT AND DOMESTIC VIOLENCE - Mahipal, Naresh; Garg, Jyoti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This book chapter examines the critical issue of women empowerment and domestic violence within the Indian legal frameworks. It delves into the historical background, legal measures, and policy interventions taken to empower women and address domestic violence in India. The chapter analyzes the impact of these programs or initiatives on women’s rights, safety and well-being. Furthermore, it discusses the challenges that persist and explores potential avenues for further reforms to promote gender equality and eliminate domestic violence in Indian society.